DLBCL of Clavicle: Role of FNA in diagnosis of Rare Lesion - Jokhi, Cyrus Dara; Vaghela, Kalpesh V; Damor, Pruthvi (Annals of Pathology and Laboratory Medicine, 2020)
Primary bone lymphoma is rare, among which commonly involved site at time of presentation are femur, pelvic bones, tibia and most common type is Large B cell lymphoma which usually occurs in adults. Cases of large B cell lymphoma in clavicle as primary bone lymphoma is extremely rare finding. According to our knowledge this case may be first reported case of world. We are here reporting a case of 62-year female presented as sternoclavicular joint swelling, without fever or pain in local area. Patient was diagnosed on X ray by radiologist, as well as by clinician as, osteosarcoma of right clavicle. Patient came to Department of Cytopathology for FNA for confirmation of X ray finding. On FNA diagnosis of Non-Hodgkin lymphoma was given, and advise for biopsy and immunohistochemistry (IHC) was given for confirmation of diagnosis and to subtype NHL. On IHC Ki67 index was 85%, with diffuse positivity noted for MUM1, CD79a, and CD138 along with cytoplasmic positivity for ALK 1 and patchy positivity for PAX 5. Tumor was negative for BCL6, BCL2, CD20, CD5, CD23, CD10, CD19, CD4, CD8, CD7, CD3. Diagnosis of ALK positive DLBCL was given on biopsy after IHC. Patients with PBL treated with combined modality were found to have a superior outcome, with a significantly better survival (5-year cause-specific survival 95%). So correct and timely pathological diagnosis of DLBCL as PBL is significantly important for prognosis.